Flower like Buffer Layer to Improve Efficiency of Submicron-Thick CuIn1-xGaxSe2 Solar Cells - 박래만; 조대형; 이규석 (ETRI journal, 2015)
In this article, a study of a flower like nanostructured CdS buffer layer for improving the performance of a submicron-thick CuIn1-xGaxSe2 (CIGS) solar cell (SC) is presented. Both its synthesis and properties are discussed in detail. The surface reflectance of the device is dramatically decreased. SCs with flower like nanostructured CdS buffer layers enhance short-circuit current density, fill factor, and open-circuit voltage. These enhancements contribute to an increase in power conversion efficiency of about 55% on average compared to SCs that don’t have a flower like nanostructured CdS buffer layer, despite them both having the same CIGS light absorbing layer. KCI Citation Count: 3